Utilization of Organic Waste Coconut Shells as an Alternative Energy Source in the Laogo Area - Arinda Ristawati; Aqlyna Fattahanisa; Puri Wijayanti; Riskaviana Kurniawati; M Mirza Ananta Ihza Hiswara (International Journal Of Community Service, 2026)
Indonesia has abundant biomass resources, one of which comes from coconut shell waste that has not been optimally utilized. Coconut shell waste has the potential to be processed into briquettes, an environmentally friendly alternative energy source with economic value. This Community Service (PKM) activity aims to improve the knowledge and skills of communities in the Laogo region in utilizing coconut shell waste into briquettes and increase their understanding of renewable energy-based business management. The activity implementation methods included outreach, briquette-making demonstrations, an initial questionnaire to determine the community's level of knowledge, and Focus Group Discussions (FGDs) to identify obstacles and find solutions appropriate to local conditions. The results of the activity showed an increase in community understanding of the briquette-making process and its use as an alternative fuel. In addition, the community also gained knowledge about managing small businesses based on waste processing. The community response to this activity was very positive, with most participants expressing interest in producing briquettes independently. Obstacles faced included limited equipment, business capital, and technical knowledge. Therefore, ongoing support from various parties is needed to improve the sustainability of businesses based on the utilization of coconut shell waste and to support the development of renewable energy at the community level.